Lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc electrode and preparation method and application thereof

By constructing the lanthanum phosphate/alginate composite gel electrolyte interface layer on the surface of the zinc electrode, the expansion, increase resistance and dendrite problems caused by electrochemical instability of the zinc anode in aqueous zinc-based energy storage devices are solved, and the uniform deposition and long-term stability of the zinc electrode are achieved, and the cycle life of the energy storage device is extended.

CN119833529APending Publication Date: 2025-04-15ZHONGYUAN ENGINEERING COLLEGE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510041495.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In aqueous zinc-based energy storage devices, due to thermodynamic and electrochemical instability, the zinc anode will spontaneously react with H2O molecules to generate hydrogen and insulating by-products, resulting in cell expansion, increased resistance, decreased zinc plating/peeling efficiency and cyclic stability, and serious corrosion and dendrite problems.

Method used

The zinc electrode was modified by the lanthanum phosphate/alginate composite gel electrolyte interface layer, and the organic/inorganic composite interface layer was constructed on the surface of the zinc electrode, and the complexing of the crosslinked gel of alginate and the lanthanum phosphate nanomaterial was achieved by achieving uniform deposition and electrochemical stability of zinc ions.

Benefits of technology

It effectively suppresses electrochemical hydrogen evolution and corrosion side reactions at the zinc anode interface, realizes uniform deposition and long-term stability of zinc electrodes, extends the cycle life of zinc-based energy storage devices, and improves the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833529A_ABST
    Figure CN119833529A_ABST
Patent Text Reader

Abstract

The invention provides a lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc electrode as well as a preparation method and application thereof, which are used for solving the problems of zinc and aqueous electrolyte interface side reaction and zinc dendrite existing in an aqueous zinc electrode. The preparation method comprises the following steps: ultrasonically dispersing lanthanum phosphate nanoparticles in deionized water to obtain turbid liquid; mixing and dissolving alginate and the turbid liquid to form a mixed colloidal solution containing lanthanum phosphate nanoparticles; and coating the mixed colloidal solution on the surface of a zinc negative electrode to form a coating layer, and drying to obtain a lanthanum phosphate / alginate inorganic-organic composite interface layer modified zinc electrode, namely the LaPO4 / Alg-Zn metal negative electrode. According to the invention, a lanthanum phosphate / alginate composite interface layer is constructed on a zinc electrode, and the interface layer can realize a composite gel electrolyte interface layer containing cross-linked alginate gel and a lanthanum phosphate nano material in an electrochemical process due to embedding in-situ induction of zinc ions in an electrolyte; the interface layer has good mechanical performance, water absorption performance and abundant network structures, and corrosion of zinc and electrochemical hydrogen evolution side reaction are effectively inhibited. The preparation method is simple, and the selected raw materials are low in cost and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aqueous zinc-based energy storage devices and relates to a zinc electrode and a zinc-based energy storage device. Background Art

[0002] The rapid consumption of fossil energy and the environmental problems it brings have promoted the use of clean energy. Energy storage systems can effectively improve the utilization rate of clean energy and help the sustainable development of energy. Electrochemical energy storage systems have been widely used in various mobile power sources and large-scale energy storage fields due to their high conversion efficiency and convenient construction. For example, lithium-ion batteries have achieved great commercial success in electronic products, electric vehicles and other fields due to their high energy density and long cycle life. However, in the field of large-scale energy storage, lithium-ion batteries still face problems such as limited lithium resources and great safety hazards. In recent years, zinc-ion batteries (AZIBs) using aqueous electrolytes have become one of the most concerned future large-scale energy storage systems due to their high safety, low cost (rich resources, easy assembly), and environmental friendliness. As one of the most widely used negative electrode materials, zinc metal anode has high theoretical specific capacity (820mAh g-1), low redox potential (-0.762V compared to standard hydrogen electrode (SHE)), safety and environmental protection, and other advantages, making it one of the most commercially promising negative electrodes for zinc-ion batteries. However, in aqueous electrolytes, the zinc anode will spontaneously react with H2O molecules to generate hydrogen and insulating byproducts due to thermodynamic and electrochemical instability, which will cause battery expansion, increased resistance, and poor efficiency and cycle stability of zinc plating / stripping. At the same time, the accumulation of corroded zinc and its byproducts will aggravate the inhomogeneity of the zinc surface, leading to uneven electric field, forming a "tip effect", and producing dendrite morphology, resulting in battery short circuit and safety issues.

[0003] Therefore, in order to suppress the dendrites and side reactions occurring at the zinc anode / electrolyte interface during the electrochemical cycle and achieve uniform zinc deposition, researchers have proposed different solutions such as constructing an artificial interface layer, designing a new zinc anode structure, and optimizing the electrolyte. 2+Uniform deposition and direct contact with the electrolyte are considered to be important ways to inhibit dendrite growth and reduce side reactions. For example, some inorganic compounds (such as CaCO3, TiO2, ZnSMOF) and organic polymer materials (such as PVDF, PANI, polyamide) are directly coated on the surface of the zinc negative electrode to improve the comprehensive electrochemical performance of the zinc negative electrode. Although some progress has been made in this research field, the current single coating technology has not yet fully achieved the comprehensive characteristics required by the ideal zinc electrode interface protective layer, such as efficient zinc ion transmission, uniform zinc ion distribution, good long-term structural stability, and good adaptability to volume changes. For example, the layer obtained by inorganic materials with the assistance of adhesives such as polyvinylidene fluoride (PVDF) has a large interface layer brittleness, which is difficult to adapt to the volume changes during zinc electroplating and stripping, and may cause the coating to break and fall off. Although some hydrophobic polymer interface layers have good flexibility and the ability to inhibit interface side reactions, their electrolyte wettability and zinc ion transmission performance need to be improved. Therefore, finding an interface protective layer that is stable in aqueous solution for a long time and has good mechanical strength and zinc ion transport performance has become the key and challenge in this field. Earlier, our research team developed a new type of zinc metal anode, whose surface is coated with a hydrophilic and corrosion-resistant lanthanum phosphate interface layer (patent application number CN202410030803.5) to inhibit the electrochemical hydrogen evolution (HER) and zinc corrosion side reactions between water and zinc anode in the interfacial electrolyte. However, the main body of the interface layer is an inorganic compound lanthanum phosphate, which lacks a network structure for zinc ion transmission, and the long-term stability of the interface layer needs to be improved. Summary of the invention

[0004] Therefore, in view of the technical difficulties that a single inorganic or organic material interface layer is difficult to simultaneously achieve efficient zinc ion transmission, uniform zinc ion deposition, long-term stability of the structure, and good adaptability to volume expansion and contraction, the present invention proposes a zinc electrode modified with a lanthanum phosphate / alginate composite gel electrolyte interface layer and its preparation method and application, in order to improve the cycle life of the zinc electrode. The present invention uses alginate and lanthanum phosphate nanoparticles as the main materials to construct an organic / inorganic composite interface layer on the surface of the zinc electrode. During the electrochemical process, the interface layer will be in situ induced by the embedding of zinc ions in the electrolyte to realize a composite gel electrolyte interface layer containing cross-linked alginate gel and lanthanum phosphate nanomaterials, aiming to solve the problems of hydrogen evolution, zinc corrosion, zinc dendrites, etc. existing in zinc electrodes for aqueous zinc-based energy storage devices, thereby improving the cycle life of zinc electrodes and aqueous zinc-based energy storage devices. The composite interface layer also has good flexibility and good mechanical strength because it contains inorganic and organic components, and can effectively improve the comprehensive performance of the zinc electrode for a long time.

[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A method for preparing a zinc electrode modified with a lanthanum phosphate / alginate composite gel electrolyte interface layer comprises the following steps:

[0007] (1) ultrasonically dispersing lanthanum phosphate nanoparticles in deionized water to form a suspension; mixing and dissolving alginate with the suspension to form a mixed colloidal solution containing lanthanum phosphate nanoparticles;

[0008] (2) coating the mixed colloidal solution on the surface of the zinc negative electrode to form a coating layer, and drying to obtain a lanthanum phosphate / alginate inorganic-organic composite interface layer modified zinc electrode, i.e., LaPO4 / Alg@Zn metal negative electrode.

[0009] Preferably, the particle size of the lanthanum phosphate nanoparticles in step (1) is 5-600 nm; and the alginate is one or both of sodium alginate and potassium alginate.

[0010] Preferably, the mass ratio of the lanthanum phosphate nanoparticles, alginate and water is 0.1-2:1.4-2.2:100.

[0011] Preferably, heating and stirring are performed during the mixed dissolution process, and the heating and stirring temperature is 25-55° C. and the time is 4 h-10 h.

[0012] Preferably, the thickness of the coating layer in step (2) is 5-100 μm, preferably the thickness of the coating is 25-100 μm, and more preferably the thickness of the coating is 50-100 μm.

[0013] Preferably, the drying temperature is 45-75° C., and the drying time is 8-24 hours.

[0014] Preferably, the preparation method of the lanthanum phosphate nanoparticles is to heat and stir a lanthanum metal salt solution and a phosphate solution until the solution becomes turbid, and then separate, wash, and dry to obtain the lanthanum phosphate nanoparticles.

[0015] The lanthanum metal salt is lanthanum nitrate, lanthanum acetate or lanthanum chloride; the phosphate is ammonium phosphate, sodium phosphate or potassium phosphate.

[0016] The concentration of the phosphate solution is 30-40 wt %, and the concentration of the lanthanum metal salt solution is 25-35 wt %.

[0017] The volume ratio of the lanthanum metal salt solution to the phosphate solution is 1:1; the heating and stirring conditions are a temperature of 40-60° C. and a time of 4-12 hours; and the drying conditions are a temperature of 60-80° C. and a time of 20-28 hours.

[0018] Preferably, the method is used to prepare a zinc electrode modified with a lanthanum phosphate / alginate composite gel electrolyte interface layer.

[0019] Preferably, the zinc electrode modified with the lanthanum phosphate / alginate composite gel electrolyte interface layer is used in an aqueous zinc-based energy storage device.

[0020] Preferably, the aqueous zinc-based energy storage device includes an aqueous zinc ion battery and an aqueous zinc ion capacitor.

[0021] The present invention has the following beneficial effects:

[0022] 1. In the present invention, the organic-inorganic composite interface layer constructed with LaPO4 nanoparticles as the skeleton and alginate can realize a composite gel electrolyte interface layer containing cross-linked alginate gel and lanthanum phosphate nanomaterials due to the in-situ induction of zinc ions embedded in the electrolyte during the electrochemical process. Thus, it has good mechanical strength and water absorption. The alginate cross-linked gel obtained by in-situ cross-linking of alginate during the electrochemical reaction has good flexibility and rich water absorption network structure. LaPO4 and alginate gel in the interface layer can play a synergistic role. The good water absorption and conductivity of LaPO4 can help improve the performance of alginate gel, and at the same time have good flexibility and certain mechanical strength; alginate has rich zinc-philic and hydrophilic carboxyl functional groups and rich and uniform network structure, which can reduce the activity of water in the electrolyte, effectively promote the desolvation and interface migration of zinc ions, and form a water-poor layer at the microscopic interface of the zinc metal electrode, thereby effectively inhibiting zinc corrosion and electrochemical hydrogen evolution side reactions. Therefore, the lanthanum phosphate / alginate composite gel electrolyte interface layer can achieve a uniform zinc deposition environment and inhibit the occurrence of interfacial side reactions; it can also effectively adapt to the volume changes of the zinc electrode during the deposition and stripping process, and has certain self-healing properties, preventing the generation of zinc dendrites and their damage to the diaphragm.

[0023] 2. The present invention can not only inhibit the activity of water in the electrolyte at the zinc anode interface, but also create a local water-poor area on the zinc anode surface because both LaPO4 nanoparticles and alginate have excellent hydrophilicity and rich porosity, thereby inhibiting electrochemical hydrogen evolution (HER) and zinc corrosion side reactions at the zinc anode interface and promoting the desolvation process of zinc ions.

[0024] 3. The alginate in the present invention has abundant zinc-philic carboxyl functional groups and rich and uniform network structures, which can effectively promote the desolvation of zinc ions and interface migration. Therefore, the lanthanum phosphate / alginate composite gel electrolyte interface layer can achieve a uniform zinc deposition environment and inhibit the occurrence of interface side reactions; it can also effectively adapt to the volume change of the zinc electrode during deposition and stripping, and has certain self-repairing properties to prevent the generation of zinc dendrites and their damage to the diaphragm.

[0025] 4. In the present invention, alginate is a polyanionic natural organic polymer, in which the carboxyl group can not only coordinate with the zinc ion center to produce a cross-linking reaction to achieve a stable electrode interface layer and uniform zinc ion flow, but also has a negatively charged polar group to promote the migration and desolvation process of zinc ions, and reduce the generation of zinc dendrites. At the same time, LaPO4 has a higher electrical conductivity, which makes up for the disadvantage of the weak conductivity of the alginate organic coating. Moreover, alginate is converted into a water-insoluble gelled interface film on the surface of the zinc anode through in-situ cross-linking, forming a dynamic adaptive interface and LaPO4 to play a complementary role, which can effectively adapt to the volume change of the zinc negative electrode during the deposition and stripping process, and can also self-repair the cracks pierced by zinc dendrites, and combined with LaPO4 to extend the life of the gelled interface film, significantly improving the cycle life of aqueous zinc ion batteries and aqueous zinc ion capacitors.

[0026] 5. The good water absorption of LaPO4 can help improve the performance of alginate gel, while also having good flexibility and certain mechanical strength; alginate has abundant zinc-philic carboxyl functional groups and a rich and uniform network structure, which can effectively promote the desolvation of zinc ions and interfacial migration. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is the EDS element spectrum of the LaPO4 / Alg@Zn metal zinc negative electrode sheet prepared in Example 1 of the present invention.

[0029] Figure 2 Figure 2 is SEM test of the LaPO4 / Alg@Zn metal zinc negative electrode sheet prepared in Example 1 of the present invention and its comparison sample (blank pure zinc negative electrode, Alg@Zn metal zinc negative electrode sheet); wherein (a), (b), (c), (d) and (e) are scanning electron microscope photos of pure zinc negative electrode, Alg@Zn negative electrode, 5% LaPO4 / Alg@Zn negative electrode, 20% LaPO4 / Alg@Zn negative electrode and 35% LaPO4 / Alg@Zn negative electrode before reaction, respectively; (f), (g), (h), (i) and (j) are scanning electron microscope photos of pure Zn negative electrode, Alg@Zn negative electrode, 5% LaPO4 / Alg@Zn negative electrode, 20% LaPO4 / Alg@Zn negative electrode and 35% LaPO4 / Alg@Zn negative electrode after being immersed in electrolyte for one month, respectively.

[0030] Figure 3 The symmetrical batteries prepared in Application Examples 1-3 of the present invention (respectively 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn and 35% LaPO4 / Alg@Zn symmetrical batteries) and Comparative Application Examples 1 and 2 have a capacity of 1 mAh cm -2 , current density is 1 mA cm -2 Long cycle performance diagram.

[0031] Figure 4 Symmetrical batteries prepared in application examples 1-3 of the present invention (respectively 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn and 35% LaPO4 / Alg@Zn symmetrical batteries) and comparative application examples 1 and 2 (Alg@Zn) have a capacity of 1 mAh cm -2 , current density is 5 mA cm -2 Long cycle performance diagram.

[0032] Figure 5 These are microscopic observation photos of in-situ dendrites of zinc deposition on pure zinc in the present invention and the LaPO4 / Alg@Zn negative electrode of Example 1.

[0033] Figure 6 LSV diagrams of symmetrical batteries prepared by Application Examples 1-3 of the present invention (respectively marked as 5% LAP-SA, 20% LAP-SA and 35% LAP-SA symmetrical batteries) and Comparative Application Example 1 (marked as pure SA) and Comparative Application Example 2 (marked as pure zinc).

[0034] Figure 7 The zinc-Ti half-cells with LaPO4 / Alg@Zn anodes corresponding to application examples 4-6 of the present invention (respectively denoted as 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn and 35% LaPO4 / Alg@Zn) and the half-cells with pure zinc and Alg@Zn of comparative example 1 as anodes have a capacity of 1 mAh cm -2 , current density is 5 mA cm -2 Long cycle performance diagram.

[0035] Figure 8 CV diagrams of zinc-Ti half-cells with LaPO4 / Alg@Zn negative electrodes corresponding to Applications 4-6 of the present invention (respectively denoted as 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, 35% LaPO4 / Alg@Zn), and half-cells assembled with pure zinc and Alg@Zn of Comparative Example 1 and Ti sheets as counter electrodes.

[0036] Fig. 9This is a performance comparison chart of 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, 35% LaPO4 / Alg@Zn zinc ion capacitors prepared in Application Examples 7-9 and Comparative Example 1 and capacitors assembled with pure zinc as the negative electrode and AC (conductive carbon), respectively.

[0037] Fig.10 Contact angle experiments of the LaPO4 / Alg@Zn metal zinc negative electrode sheets prepared in Examples 1-3 of the present invention and their control samples (blank pure zinc negative electrode, Alg@Zn metal zinc negative electrode sheets) with electrolyte and water, respectively; (a)(b)(c)(d)(e) are the contact angles of pure zinc, Alg@Zn, 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, 35% LaPO4 / Alg@Zn negative electrodes and water; (f)(g)(h)(i)(j) are the contact angles of pure Zn, Alg@Zn, 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, 35% LaPO4 / Alg@Zn negative electrodes and electrolyte, respectively. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The raw materials used in the embodiments of the present invention are commercially available products.

[0040] Example 1

[0041] This embodiment is a method for preparing a hydrophilic lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc electrode, the steps are as follows:

[0042] (1) Dissolve 55g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) in 100ml of deionized water and stir for 15min to form a uniform solution, which is recorded as solution A. Then weigh 50g of ammonium dihydrogen phosphate (NH4H2PO4) and dissolve it in 100ml of deionized water. Stir for 15min to form a uniform solution, which is recorded as solution B. Add solution A dropwise to solution B and heat and stir at 50℃ for 8h until the mixed solution becomes turbid. Then, after centrifugal washing, dry the obtained substance at 75℃ for 24h to obtain 100nm LaPO4 nanoparticles.

[0043] (2) 0.1 g of 100 nm LaPO4 powder was added to 100 mL of deionized water and uniformly dispersed to obtain a LaPO4 suspension. Subsequently, 1.875 g of alginate was added to the above LaPO4 suspension and heated and stirred at 55°C for 4 h until a uniform viscous mixed colloidal solution was formed.

[0044] (3) The uniform viscous mixed colloidal solution was coated on the surface of the zinc sheet with a 250 μm square scraper, and then dried at 45° C. for 24 h to obtain a 5% LaPO4 / Alg@Zn metal anode with a coating layer thickness of 100 μm.

[0045] Comparative Example 1

[0046] This comparative example provides a method for preparing an Alg@Zn metal negative electrode, which is different from Example 1 in that LaPO4 modification is not added to prepare an Alg@Zn metal negative electrode. The specific steps are:

[0047] (1) Add 1.875 g of alginate to 100 mL of deionized water and heat and stir at 55 °C for 4 h until a uniform viscous mixed colloidal solution is formed.

[0048] (2) The uniform viscous mixed colloidal solution was coated on the surface of the zinc sheet with a 250 μm square scraper, and then dried at 45°C for 8 h to obtain an Alg@Zn metal anode with a coating layer thickness of 100 μm.

[0049] Figure 1 This is the EDS element spectrum of the composite gel electrolyte interface layer modified zinc negative electrode prepared in Example 1 of the present invention.

[0050] Figure 2 The present invention is a scanning electron microscope comparison of the zinc negative electrode modified with the lanthanum phosphate / alginate composite gel electrolyte interface layer prepared in Example 1 of the present invention, the blank zinc negative electrode of the comparative example, and the coated Alg@Zn negative electrode before and after the reaction at the same scale; wherein (a), (b), (c), (d) and (e) are scanning electron microscope photographs of the pure zinc negative electrode, Alg@Zn negative electrode, 5% LaPO4 / Alg@Zn negative electrode, 20% LaPO4 / Alg@Zn negative electrode and 35% LaPO4 / Alg@Zn negative electrode before the reaction, respectively; (f), (g), (h), (i) and (j) are scanning electron microscope photographs of the pure Zn negative electrode, Alg@Zn negative electrode, 5% LaPO4 / Alg@Zn negative electrode, 20% LaPO4 / Alg@Zn negative electrode and 35% LaPO4 / Alg@Zn negative electrode after being immersed in 3M ZnSO4 electrolyte for one month, respectively.

[0051] From (a), (b) and (c), we can see that the surfaces of the blank Zn negative electrode, the Alg@Zn coated negative electrode and the 5% LaPO4 / Alg@Zn coated negative electrode are relatively flat before the reaction, and the surface of the LaPO4 / Alg@Zn coated negative electrode is relatively dense and has LaPO4 particles; from (f), we can see that the surface of the blank Zn negative electrode is not flat after the reaction, and there are a lot of irregular vertical dendrite byproducts that are particularly large and thick, which may cause the battery to short circuit; from (g), we can see that the surface of the Alg@Zn coated negative electrode is not flat after the reaction, and there are a lot of vertical dendrites that are relatively small and thin, which may reduce the battery life; but from (h), we can see that there is no obvious vertical dendrite byproduct on the surface of the electrode sheet after the 5% LaPO4 / Alg@Zn coated negative electrode is cycled, the surface is relatively flat, and the zinc deposition is relatively good. It can be seen that the modification of the zinc negative electrode with the lanthanum phosphate / alginate composite gel electrolyte interface layer can change the growth direction of the byproducts on the surface of the Zn negative electrode during the reaction, thus avoiding the generation of vertical dendrites. By comparing with the reference samples (blank pure zinc negative electrode, Alg@Zn metal negative electrode), it is found that the LaPO4 / Alg@Zn metal negative electrode prepared by the present invention has a smooth electrode surface before and after the reaction, and no vertical dendrites are found ( Figure 2 h, i, j), while the blank pure zinc negative electrode showed a particularly large and thick irregular vertical dendrites after the reaction ( Figure 2 f), the Alg@Zn metal anode has an uneven surface after reaction, and has many small and thin vertical dendrites ( Figure 2 g), which confirms that the LaPO4 / Alg@Zn metal anode prepared by the present invention effectively inhibits the growth of zinc dendrites.

[0052] Example 2

[0053] This example is the preparation of a lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc negative electrode (LaPO4 / Alg@Zn metal negative electrode), the steps are as follows:

[0054] (1) Dissolve 50g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) in 100ml of deionized water and stir for 15min to form a uniform solution, which is recorded as solution A. Then weigh 45g of ammonium dihydrogen phosphate (NH4H2PO4) and dissolve it in 100ml of deionized water. Stir for 15min to form a uniform solution, which is recorded as solution B. Add solution A dropwise to solution B, heat and stir at 55℃ for 10h until the mixed solution becomes turbid. Then, after centrifugation and washing, dry the obtained substance at 70℃ for 25h to obtain 150nm LaPO4 nanoparticles.

[0055] (2) 0.5 g of 150 nm LaPO4 powder was added to 100 mL of deionized water and uniformly dispersed to obtain a LaPO4 suspension. Subsequently, 1.975 g of alginate was added to the above LaPO4 suspension and heated and stirred at 45°C for 6 h until a uniform viscous mixed colloidal solution was formed.

[0056] (3) The uniform viscous mixed colloidal solution was coated on the surface of the zinc sheet with a 250 μm square scraper, and then dried at 55° C. for 12 h to obtain a 20% LaPO4 / Alg@Zn metal anode with a coating layer thickness of 75 μm.

[0057] Example 3

[0058] This example is the preparation of a lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc negative electrode (LaPO4 / Alg@Zn metal negative electrode), the steps are as follows:

[0059] (1) Dissolve 45g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) in 100ml of deionized water and stir for 15min to form a uniform solution, which is recorded as solution A. Then weigh 35g of ammonium dihydrogen phosphate (NH4H2PO4) and dissolve it in 100ml of deionized water. Stir for 15min to form a uniform solution, which is recorded as solution B. Add solution A dropwise to solution B and heat and stir at 60℃ for 12h until the mixed solution becomes turbid. Then, after centrifugal washing, dry the obtained substance at 65℃ for 26h to obtain 600nm LaPO4 nanoparticles.

[0060] (2) 1 g of 600 nm LaPO4 powder was added to 100 mL of deionized water and uniformly dispersed to obtain a LaPO4 suspension. Subsequently, 1.85 g of alginate was added to the above LaPO4 suspension and heated and stirred at 35°C for 8 h until a uniform viscous mixed colloidal solution was formed.

[0061] (3) The uniform viscous mixed colloidal solution was coated on the surface of the zinc sheet with a 150 μm square scraper, and then dried at 65° C. for 16 h to obtain a 35% LaPO4 / Alg@Zn metal anode with a coating layer thickness of 50 μm.

[0062] Example 4

[0063] This example is the preparation of a lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc negative electrode (LaPO4 / Alg@Zn metal negative electrode), the steps are as follows:

[0064] (1) Dissolve 60g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) in 100ml of deionized water and stir for 15min to form a uniform solution, which is recorded as solution A. Then weigh 55g of ammonium dihydrogen phosphate (NH4H2PO4) and dissolve it in 100ml of deionized water. Stir for 15min to form a uniform solution, which is recorded as solution B. Add solution A dropwise to solution B and heat and stir at 45℃ for 6h until the mixed solution becomes turbid. Then, after centrifugal washing, dry the obtained substance at 60℃ for 27h to obtain 50nm LaPO4 nanoparticles.

[0065] (2) 1.5 g of 50 nm LaPO4 powder was added to 100 mL of deionized water and uniformly dispersed to obtain a LaPO4 suspension. Subsequently, 1.4 g of alginate was added to the above LaPO4 suspension and heated and stirred at 25°C for 10 h until a uniform viscous mixed colloidal solution was formed.

[0066] (3) The uniform viscous mixed colloidal solution was coated on the surface of the zinc sheet with a 150 μm square scraper, and then dried at 75°C for 20 h to obtain a 50% LaPO4 / Alg@Zn metal anode with a coating layer thickness of 25 μm.

[0067] Aqueous zinc sulfate electrolyte was used, glass fiber was used as a separator, and the 50% LaPO4 / Alg@Zn metal negative electrode prepared in Example 4 was used as an electrode sheet to assemble a zinc / / zinc symmetric battery, and the cycle performance and polarization potential were tested.

[0068] Using aqueous zinc sulfate electrolyte and glass fiber as separator, 50% LaPO4 / Alg@Zn metal anode and activated carbon (AC) were assembled into capacitors to test capacity, rate performance and cycle stability.

[0069] Example 5

[0070] This example is the preparation of a lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc negative electrode (LaPO4 / Alg@Zn metal negative electrode), the steps are as follows:

[0071] (1) Dissolve 65g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) in 100ml of deionized water and stir for 15min to form a uniform solution, which is recorded as solution A. Then weigh 60g of ammonium dihydrogen phosphate (NH4H2PO4) and dissolve it in 100ml of deionized water. Stir for 15min to form a uniform solution, which is recorded as solution B. Add solution A dropwise to solution B and heat and stir at 40℃ for 4h until the mixed solution becomes turbid. Then, after centrifugal washing, dry the obtained substance at 60℃ for 28h to obtain 5nm LaPO4 nanoparticles.

[0072] (2) Add 2 g of 5 nm LaPO4 powder to 100 mL of deionized water and disperse uniformly to obtain a LaPO4 suspension. Then, add 2.2 g of alginate to the above LaPO4 suspension and heat and stir at 25°C for 10 h until a uniform viscous mixed colloidal solution is formed.

[0073] (3) The uniform viscous mixed colloidal solution was coated on the surface of the zinc sheet with a 100 μm square scraper, and then dried at 75°C for 24 h to obtain a LaPO4 / Alg@Zn metal anode with a coating layer thickness of 5 μm.

[0074] Application Examples 1-3

[0075] Application of LaPO4 / Alg@Zn metal anode in aqueous zinc ion batteries:

[0076] The LaPO4 / Alg@Zn metal negative electrodes prepared in Examples 1-3 were punched into discs with a diameter of 8 mm, glass fiber was used as a separator, 2M ZnSO4 solution was used as an electrolyte, metal gaskets and springs were used as filling materials, CR-2032 button-type symmetrical batteries were assembled and packaged using a packaging machine, corresponding to Application Examples 1-3, and then left to stand for 7 hours before the electrochemical performance test was performed. The zinc deposition / stripping performance was tested on a blue electric charge and discharge tester using a constant current method to characterize its cycle performance and polarization potential.

[0077] Comparative application example 1

[0078] The difference from Application Example 1 is that this comparative application example 1 uses the Alg@Zn of Comparative Example 1 as the zinc negative electrode and then assembles it into a symmetrical battery, and the steps are as follows:

[0079] The Alg@Zn metal negative electrode was punched into a disc with a diameter of 8 mm, and glass fiber was used as a separator, 2M ZnSO4 solution was used as an electrolyte, and metal gaskets and springs were used as filling materials to assemble CR-2032 button-type symmetrical cells and packaged using a packaging machine. Then, the cells were left to stand for 12 hours before the electrochemical performance test was performed. The deposition / stripping performance of the cells was tested on a blue-electric charge and discharge tester using a constant current method to characterize their cycling performance and polarization potential.

[0080] Comparative Application Example 2

[0081] The difference from Application Example 1 is that this comparative application example 2 uses a pure Zn metal sheet as the zinc negative electrode and then assembles it into a symmetrical battery, and the steps are as follows:

[0082] The pure zinc metal sheet was punched into discs with a diameter of 8 mm, glass fiber was used as a separator, 2M ZnSO4 solution was used as an electrolyte, metal gaskets and springs were used as filling materials, CR-2032 button cells were assembled and packaged using a packaging machine, and then left to stand for 12 hours before the electrochemical performance test was performed. The deposition / stripping performance of the battery was tested on a blue electric charge and discharge tester using a constant current method to characterize its cycle performance and polarization potential.

[0083] Figure 3 , 4 The symmetrical batteries with 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, and 35% LaPO4 / Alg@Zn modified zinc negative electrodes and the symmetrical batteries with Alg@Zn negative electrodes in comparative application example 1 and pure zinc negative electrodes in comparative application example 2 have a capacity of 1 mAh cm -2 , current density is 1mAcm -2 and a capacity of 1 mAh cm -2 , current density is 5mAcm -2 The long cycle performance diagram of the two symmetrical batteries assembled with the pure zinc anode of comparative application example 2 and the Alg@Zn anode of comparative application example 1 is 1mA / cm 2 The current density and 1 mAh / cm 2 Comparison of the cycling stability of the deposition / stripping curves at the capacity of Figure 3 ), and at 5 mA / cm 2 The current density and 1 mAh / cm 2 Long cycle comparison of deposition / stripping curves at a capacity of Figure 4 ). It can be seen from the figure that: Application Example 1 at 1mA / cm 2 Current density, 1 mAh / cm 2 After 2000h of cycling at low capacity, the battery still maintained a good operating state; however, the pure zinc anode (Comparative Application Example 2) and the Alg@Zn anode (Comparative Application Example 1) showed charge and discharge fluctuations from 20h and 300h respectively, and the battery short-circuited at 50h and 400h, making it difficult to cycle stably. The symmetrical battery assembled with 5% LaPO4 / Alg@Zn modified zinc anode prepared by the present invention (Application Example 1) showed a stable operation at 5mA / cm 2 At a current density of , it showed better cycle stability ( Figure 4); The blank pure Zn / / Zn symmetrical battery had a sudden drop / surge in polarization voltage when it was cycled for 120h, which may be caused by a short circuit in the battery. In addition, the Alg@Zn symmetrical battery also had a short circuit phenomenon and a sudden drop / surge in polarization voltage when it was cycled for 500h, which may be caused by a short circuit in the battery. In contrast, the LaPO4 / Alg@Zn symmetrical battery of the present invention still showed a stable polarization voltage curve after cycling for 1600h, showing the best cycle stability. It is proved that the LaPO4 / Alg@Zn prepared by the present invention improves the stability and uniform stripping plating of zinc ion batteries, showing the best cycle stability.

[0084] Figure 5 In-situ dendrite microscopy test of the Alg@Zn modified zinc anode and pure zinc electrode prepared in Application Example 1. As can be seen from the figure, LSV test was also performed for further comparison ( Figure 6 ).from Figure 5 and Figure 6 In the LSV and in-situ dendrite microscope tests, Application Example 1 showed excellent inhibition of hydrogen evolution and zinc dendrites, inducing a relatively uniform deposition of zinc ions on the surface, proving that the Alg@Zn prepared by the present invention improves the safety of zinc ion batteries and uniform stripping and plating.

[0085] The LaPO4 / Alg@Zn prepared by the present invention has a better effect of inhibiting hydrogen evolution. Figure 6 As shown, by testing the LSV curves of LaPO4 / Alg@Zn prepared by the present invention and pure zinc, it is found that LaPO4 / Alg@Zn helps to inhibit electrochemical hydrogen evolution (HER) at the zinc anode interface, while pure zinc has a more serious hydrogen evolution phenomenon. We know that a better hydrogen evolution inhibition effect can reduce the generation of hydrogen inside the battery and improve the coulombic efficiency of the battery, because more charge is used for the deposition and stripping of zinc ions instead of for the generation of hydrogen, thereby enhancing the stability of the battery and extending the cycle life, reducing the risk of battery expansion and rupture, and improving the safety of the battery, which can promote its commercial application and large-scale promotion, and is of great significance to practical applications and energy storage fields.

[0086] Application Examples 4-6

[0087] The zinc-Ti half-cell assembly of LaPO4 / Alg@Zn anode is as follows:

[0088] The 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, and 35% LaPO4 / Alg@Zn negative electrodes prepared in Example 1, Example 2, and Example 3 were punched into discs with a diameter of 8 mm, and a 12 mm Ti sheet was used as the counter electrode, glass fiber was used as the separator, 2M ZnSO4 solution was used as the electrolyte, and metal gaskets and springs were used as filling materials to assemble CR-2032 button cells and packaged using a packaging machine, corresponding to Application Examples 4-6 respectively; then the cells were left to stand for 12 hours before the electrochemical performance test was performed. The deposition / stripping performance of the cell was tested on a blue electric charge and discharge tester using a constant current method to characterize its cycle performance and polarization potential.

[0089] Figure 7 The deposition / stripping curves of the half-cells assembled with Ti sheets for the 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, 35% LaPO4 / Alg@Zn negative electrodes prepared in Examples 4-6 and the negative electrodes in Comparative Example 1 and pure zinc, respectively, at 5 mA / cm 2 After 2000 cycles, the average Coulombic efficiency of the half-cell assembled with LaPO4 / Alg@Zn was 99.5%, while the half-cell assembled with pure zinc and comparative example 1 became disordered after 400 and 800 cycles, respectively, and the Coulombic efficiency was significantly reduced.

[0090] Figure 8 The CV curves of the half-cells assembled with Ti sheets are 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, 35% LaPO4 / Alg@Zn negative electrodes prepared in Examples 4-6 and pure zinc negative electrodes prepared in Comparative Example 1. The CV curves ( Figure 8 ), compared with Comparative Example 1 and the pure zinc half-cell, the LaPO4 / Alg@Zn half-cell exhibits a smaller overpotential and a higher response current during the plating / stripping process, indicating faster Zn deposition / dissolution kinetics.

[0091] Application Example 7

[0092] Application of LaPO4 / Alg@Zn metal negative electrode in zinc ion capacitors:

[0093] The 5% LaPO4 / Alg@Zn metal anode prepared in Example 1 was punched into discs with a diameter of 8 mm. AC, acetylene black and binder (PVDF) were coated on titanium foil in a slurry with a mass ratio of 7:2:1. After vacuum drying at 80 °C, the electrode sheets were cut into 8 mm diameter sheets. The active loading was controlled at 1-2 mg cm -2, used as the positive electrode. Using glass fiber as the diaphragm, 2MZnSO4 solution as the electrolyte, metal gaskets and springs as the filling materials, CR-2032 button capacitors were assembled and packaged with a packaging machine, and then left to stand for 7 hours before the electrochemical performance test.

[0094] Application Example 8, Application Example 9

[0095] Using the method of Application Example 7, the 20% LaPO4 / Alg@Zn and 35% LaPO4 / Alg@Zn negative electrodes prepared in Examples 2 and 3 were assembled into corresponding zinc ion capacitors, corresponding to Application Example 8 and Application Example 9, respectively.

[0096] Fig. 9 Performance comparison of AC (conductive carbon) capacitors assembled with 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, 35% LaPO4 / Alg@Zn negative electrodes prepared in Application Examples 7-9 and Comparative Example 1 and pure zinc as negative electrodes. Cycle efficiency and discharge specific capacity under 1A / g test conditions. After 4500 cycles at 1A / g, the reversible capacity of the 20% LaPO4 / Alg@Zn capacitor remains at 46mAh / g, and the coulombic efficiency is 99.5%, while the capacity of the pure zinc negative electrode and the corresponding AC capacitor of Comparative Example 1 drops rapidly after 400 and 3500 cycles, respectively.

[0097] Fig.10 The contact angle experiments of 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn, 35% LaPO4 / Alg@Zn negative electrodes, Alg@Zn and pure zinc negative electrodes prepared in Examples 1-3 with water and electrolyte, respectively. (a), (b), (c), (d) and (e) are the contact angles on the negative electrodes of pure zinc, Alg@Zn, 5% LaPO4 / Alg@Zn, 20% LaPO4 / Alg@Zn and 35% LaPO4 / Alg@Zn, respectively. It can be seen from the figure that compared with the pure zinc electrode, the contact angles of Alg@Zn and LaPO4 / Alg@Zn negative electrodes are getting smaller and smaller; (f)(g)(h)(i)(j) are the contact angles of 2M ZnSO4 electrolyte on the zinc negative electrode. It can be seen from the figure that compared with the pure zinc electrode, the contact angles of Alg@Zn and LaPO4 / Alg@Zn negative electrodes are getting smaller and smaller. It is proved that it has the property of hydrophilicity and water retention, which not only prolongs the life of the interface film, but also has excellent electrolyte wettability.

[0098] The zinc negative electrodes prepared in Examples 1-5 and Comparative Example 1 were used to prepare symmetrical batteries and capacitors. The preparation process and cycle performance are shown in Table 1:

[0099]

[0100] It can be seen from the above table that the zinc negative electrode prepared by the present invention is used in zinc symmetrical batteries, which significantly improves the cycle life of batteries and capacitors.

[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a zinc electrode modified with a lanthanum phosphate / alginate composite gel electrolyte interface layer, characterized in that: The steps include: (1) ultrasonically dispersing lanthanum phosphate nanoparticles in deionized water to form a suspension; mixing and dissolving alginate with the suspension to form a mixed colloidal solution containing lanthanum phosphate nanoparticles; (2) coating the mixed colloidal solution on the surface of the zinc negative electrode to form a coating layer, and drying to obtain a lanthanum phosphate / alginate inorganic-organic composite interface layer modified zinc electrode, i.e., LaPO4 / Alg@Zn metal negative electrode.

2. The method for preparing the lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc electrode according to claim 1, characterized in that: The particle size of the lanthanum phosphate nanoparticles in step (1) is 5-600 nm.

3. The method for preparing the lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc electrode according to claim 1, characterized in that: The alginate is one or both of sodium alginate and potassium alginate.

4. The method for preparing a zinc electrode modified with a lanthanum phosphate / alginate composite gel electrolyte interface layer according to claim 1, characterized in that: The mass ratio of the lanthanum phosphate nanoparticles, alginate and water is 0.1-2:1.4-2.2:

100.

5. The method for preparing the lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc electrode according to claim 3, characterized in that: The mixing and dissolving process is heated and stirred, and the heating and stirring temperature is 25-55° C. and the time is 4h-10h.

6. The method for preparing the lanthanum phosphate / alginate composite gel electrolyte interface layer modified zinc electrode according to claim 1, characterized in that: The thickness of the coating layer in step (2) is 5-100 μm.

7. The method for preparing a zinc electrode modified with a lanthanum phosphate / alginate composite gel electrolyte interface layer according to claim 1, characterized in that: The drying temperature is 45-75° C., and the drying time is 8-24 hours.

8. A zinc electrode modified with a lanthanum phosphate / alginate composite gel electrolyte interface layer prepared by the method according to any one of claims 1 to 7.

9. Use of the zinc electrode modified with the lanthanum phosphate / alginate composite gel electrolyte interface layer as claimed in claim 8 in an aqueous zinc-based energy storage device.

10. The use according to claim 9, characterized in that: The aqueous zinc-based energy storage device includes an aqueous zinc ion battery and an aqueous zinc ion capacitor.

Citation Information

Patent Citations

  • Preparation method and application of hydrophilic corrosion-resistant LaPO4 interface layer modified zinc metal anode

    CN117831964A